Rhodococcus equi infection after reduction mammaplasty in an immunocompetent patient - Sandkovsky, Uriel; Sandkovsky, Gabriel; Sordillo, Emilia M.; Polsky, Bruce (Revista do Instituto de Medicina Tropical de São Paulo, 2011)
The majority of infections caused by R. equi occur in hosts with some degree of cell-mediated immunodeficiency. Immunocompetent individuals are infrequently affected and usually present with localized disease. Infections of the skin or related structures are uncommon and are usually related to environmental contamination. The microbiology laboratory plays a key role in the identification of the organism since it may be mistaken for common skin flora. We describe a 31 year-old woman without medical problems who presented nine weeks after breast reduction with right breast cellulitis and purulent drainage from the surgical wound. She underwent incision and drainage, and cultures of the wound yielded Rhodococcus equi. The patient completed six weeks of antimicrobial therapy with moxifloxacin and rifampin with complete resolution.